Case Report: Fading Elk Syndrome in a Herd of Captive Elk (Cervus elaphus) in the North American Midwest - Boggiatto, Paola M.; Crawford, Lauren S.; Kanipe, Carly; Palmer, Mitchell V.; Olsen, Steven C. (Frontiers in Veterinary Science, 2020)
Fading elk syndrome, or chronic ill-thrift of elk, is a disease associated with abomasal parasitism with Ostertagia species, of which elk appear to be particularly susceptible. While this syndrome has been extensively reported to affect wapiti-type red deer hybrids farmed in New Zealand since the mid 1980’s, there is only a single report of this disease in North America. Here we report a case of fading elk syndrome in a herd of 34 elk (Cervus elaphus) in Ames, Iowa, at the National Animal Disease Center. Analysis of complete blood counts were unremarkable, but blood chemistry demonstrated a severe hypoalbuminemia. Fecal floatation’s were also unremarkable, and non-diagnostic. Histological examination of tissues collected at necropsy revealed proliferative abomasitis and nematodes consistent with Ostertagia spp. Anthelmintic treatment consisting of a combination of pour-on Cydectin® and injectable Noromectin Plus®, at double the recommended dose for cattle, showed positive results, as all remaining animals in the herd recovered. The work presented here is the first report of naturally-acquired disease in a herd of captive elk used for research and sheds light on this seldomly-reported disease in North America.